2007
DOI: 10.1016/j.agwat.2006.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Combining FAO-56 model and ground-based remote sensing to estimate water consumptions of wheat crops in a semi-arid region

Abstract: Please cite this article in press as: Er-Raki, S. et al., Combining FAO-56 model and ground-based remote sensing to estimate water consumptions of wheat crops in a semi-arid region, Agric. Water Manage. (2006),

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
157
0
11

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 248 publications
(177 citation statements)
references
References 24 publications
9
157
0
11
Order By: Relevance
“…Many attempts have been made in this direction, with new algorithms proposed to address these other factors. Recently, many studies were conducted to obtain ET and Kc values from remote sensing [39] using the normalized difference vegetation index NDVI [40,41] and its relationship with LAI [42]. Using the improved temporal (five days with Sentinel 2A-B) and spatial (10 m in the visible and infrared region) resolution, ET estimates have the potential to provide crop water requirements over vast areas, as discussed in another contribution to this Special Issue [43].…”
Section: Need For Et Data and Simple Et Modelling Approaches In Irrigmentioning
confidence: 99%
“…Many attempts have been made in this direction, with new algorithms proposed to address these other factors. Recently, many studies were conducted to obtain ET and Kc values from remote sensing [39] using the normalized difference vegetation index NDVI [40,41] and its relationship with LAI [42]. Using the improved temporal (five days with Sentinel 2A-B) and spatial (10 m in the visible and infrared region) resolution, ET estimates have the potential to provide crop water requirements over vast areas, as discussed in another contribution to this Special Issue [43].…”
Section: Need For Et Data and Simple Et Modelling Approaches In Irrigmentioning
confidence: 99%
“…Some examples of this approach consider a linear relationship between Kcb and NDVI [13,20,25,27,28], and between Kcb and SAVI [13,25,26] but an exponential relationship between NDVI and Kc was also considered [29]. A few studies report a Kcb estimation based on fc or LAI obtained through VI, including for field and tree crops [7,30,31]. However, in most studies, the relationship between Kcb and VI was established for non-stressed conditions and for conditions of dry soil surface, which often do not represent the actual conditions of crop management.…”
Section: Introductionmentioning
confidence: 99%
“…Over the growing season results indicated that NDVI had a relationship with K cb for wheat for a semi-arid region in Morocco [Er-Raki et al, 2007]. The…”
Section: Evapotranspiration Estimationmentioning
confidence: 84%